Expanding the Morphologic, Clinical, and Molecular Spectrum of Succinate Dehydrogenase A (SDHA)-Deficient Renal Cell Carcinoma - Shivani Kandukuri; Anandi Lobo; Harrison Tsai; Manju Aron; Shilpy Jha; Michelle S. Hirsch; Sambit Mohanty (American Journal of Surgical Pathology, 2026)
Succinate dehydrogenase (SDH)-deficient renal cell carcinoma (RCC) is defined by mutations in SDH subunits (A, B, C, or D) and is associated with hereditary paraganglioma-pheochromocytoma syndrome and gastrointestinal stromal tumors (GISTs) in some patients. This multi-institutional study analyzed 5 SDHA-deficient RCCs using morphology, immunohistochemistry (IHC), and next-generation sequencing (NGS). Patients had a median age of 40 years with male predominance (4:1). Initially, tumors were diagnosed as SDHA-deficient RCC (1), collecting duct carcinoma (1), or high-grade RCC, NOS (3). NGS subsequently identified 4 tumors as SDHA-deficient RCC. Common histologic features included papillary (100%) and nested (100%) architecture, solid growth (80%), eosinophilic/flocculent cytoplasm (100%), cytoplasmic vacuoles with inclusions (80%), and nuclear grooves (20%). Four of 5 tumors were high-grade (ISUP/WHO grade 3) with desmoplastic stroma and occasional inflammation. All tumors showed loss of SDHB expression (5/5), while SDHA expression was lost in 4/5, demonstrating that SDHA IHC may be preserved despite SDHA mutation. NGS identified SDHA mutations in four tumors. During follow-up, 2 of 4 patients developed metastases within 14 to 34 months, whereas the remaining 2 had no spread after 11 to 19 months. SDHA-deficient RCC displays a spectrum from classic SDHB-deficient RCC morphology to heterogeneous high-grade tumors. It should be considered in high-grade RCCs, particularly RCC NOS with papillary or collecting duct carcinoma-like morphology and vacuolated tumor cells. NGS is recommended, especially when SDHB loss is detected, as SDHA IHC may be retained. Unlike most SDHB-deficient RCCs, SDHA-deficient RCC appears more aggressive, with increased metastatic risk and poorer prognosis.